2014
DOI: 10.1017/bec.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

(In)variability of Attachment in Middle Childhood: Secure Base Script Evidence in Diary Data

Abstract: Secure attachment is characterised by a secure base script regarding the attachment figure as a source for support. Having such a cognitive script should affect the stability of state attachment. Specifically, incongruent attachment-related information should get assimilated to this secure base script, leading to state attachment scores that hardly fluctuate. For children without a script, state attachment should vary depending on the quality of attachment-related interactions. Two diary studies were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…First, adolescents report more depressive symptoms and more insecure attachment with increasing age. This is not surprising given the findings from previous research that (a) there is an increased prevalence of depression in adolescence (Lee et al., ), and that (b) there is an increase in parent–adolescent conflicts (Paikoff & Brooks‐Gunn, ) that affect insecure adolescents' attachment expectations (Bosmans, Van de Walle, Goossens, & Ceulemans, ). Second, insecure attachment expectations and depressive symptoms were strongly related.…”
Section: Discussionmentioning
confidence: 69%
“…First, adolescents report more depressive symptoms and more insecure attachment with increasing age. This is not surprising given the findings from previous research that (a) there is an increased prevalence of depression in adolescence (Lee et al., ), and that (b) there is an increase in parent–adolescent conflicts (Paikoff & Brooks‐Gunn, ) that affect insecure adolescents' attachment expectations (Bosmans, Van de Walle, Goossens, & Ceulemans, ). Second, insecure attachment expectations and depressive symptoms were strongly related.…”
Section: Discussionmentioning
confidence: 69%
“…Children and adults vary considerably in the extent to which attachment styles remain consistent over time (Bosmans et al 2014b;Thompson 2000). Besides specific contexts, Davila et al (1997) found that also specific personality characteristics accounted for the degree of change in adult attachment representations over a 2-year time period.…”
Section: Attachment Middle Childhood State Maternal Supportmentioning
confidence: 99%
“…Only one previous study investigated state attachment in middle childhood (Bosmans et al 2014b). In the latter study, children reported day-to-day fluctuations in state trust in maternal support and whether or not they experienced conflicts with their mother during the past day.…”
Section: Attachment Middle Childhood State Maternal Supportmentioning
confidence: 99%
“…Children who trust in parents as a secure base will continue to experience trust over time. By contrast, children who lack secure base trust will fluctuate in their trust appraisals over time—for example, after a conflict, their trust decreases (Bosmans, Van de Walle, Goossens, & Ceulemans, ).…”
Section: Parent–child Secure Attachment In Middle Childhoodmentioning
confidence: 99%